2021
DOI: 10.21203/rs.3.rs-867250/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Micronized Bamboo Powder on Growth Performance, Serum Biochemical Indexes, Cecal Chyme Microflora and Metabolism of Broilers Aged 1-22 Days

Abstract: Necrotic enteritis is common in broilers, which makes negative effects on growth performance. Adding insoluble fiber to diet of broilers has been reported to improve intestinal health and promote growth performance. Bamboo powder is a cheap raw material with rich insoluble fiber. This study aims to explore the effects of feeding micronized bamboo powder (MBP) on growth performance, serum biochemical indexes, intestinal microflora, and metabolism of broilers. A total of 1440 1-day-old ephedra chickens were rand… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…In addition, the 5.0% FBP addition diet decreased the F:G compared to the pigs fed the 10% FBP addition diet. This was consistent with the previous study reported by Dai, et al [ 22 ], where the weaned piglets fed diets with 1% micronized bamboo powder addition increased their ADG but decreased their F:G compared with the CON diet. Similarly, another study revealed that 1% micronized bamboo powder could also improve the growth performance of broilers in an antibiotic-free basal diet [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the 5.0% FBP addition diet decreased the F:G compared to the pigs fed the 10% FBP addition diet. This was consistent with the previous study reported by Dai, et al [ 22 ], where the weaned piglets fed diets with 1% micronized bamboo powder addition increased their ADG but decreased their F:G compared with the CON diet. Similarly, another study revealed that 1% micronized bamboo powder could also improve the growth performance of broilers in an antibiotic-free basal diet [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Metabolic energy (ME) in the diets of the Group D and F was the same, with according to the assumption that the energy value of MBP was equivalent to that of corn under the condition of appropriate addition. Our previous reports showed that adding 1% of MBP to replace equivalent corn had no negative impact on the growth performance of piglets and young broilers (Dai et al 2021;Dai et al 2022).…”
Section: Diet Ingredients and Nutrition Levelmentioning
confidence: 94%
“…Bamboo powder can be used in the feed of ruminants after fermentation (Okano et al 2009;Oguri et al 2013), while few report has been performed on its feeding value for Monogastric animals. Our previous study revealed that adding 1% of micronized bamboo powder (MBP) to replace equivalent corn can improve the growth performance of weaned piglets, and the improvement effect of super-MBP is higher than that of general-MBP (Dai et al 2021). Meanwhile, MBP is expected to be used as a functional dietary ber raw material for broiler to reduce feed costs and improve breeding e ciency.…”
Section: Introductionmentioning
confidence: 99%